2018
DOI: 10.4067/s0717-95022018000200544
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Features of Vertebrobasilar Arterial System in Adult Black Kenyans

Abstract: OGENG'O, J. A.; MWACHAKA, P. M.; ODHIAMBO, D. E.; SINKEET, S. R.; ELBUSAIDY, H.; OLABU, B. & INYIMILI, M.Geometric features of vertebrobasilar arterial system in adult black Kenyans. Int. J. Morphol., 36(2):544-550, 2018. SUMMARY: Geometric features of vertebrobasilar system influence occurrence of posterior circulation atherosclerosis, aneurysms, stroke and neuroradiological procedures. These features show ethnic variation, but data from black Africans in Sub Saharan Africa are scarce. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Ogeng'o et al found the length, diameter, conflux, and bifurcation angles exhibiting sexually dimorphic pattern, with the BA being notably wider for 4.5 mm and longer for mean length 27.1 mm in females contrasted to men. [23] Additionally, 79.8% of conflux occurred at the bulbopontine sulcus, comparable to the Indians but much higher than in the Polish and Turkish populations. Therefore, females may be more susceptible to atherosclerosis of the VB junction.…”
Section: Epidemiologymentioning
confidence: 72%
See 1 more Smart Citation
“…Ogeng'o et al found the length, diameter, conflux, and bifurcation angles exhibiting sexually dimorphic pattern, with the BA being notably wider for 4.5 mm and longer for mean length 27.1 mm in females contrasted to men. [23] Additionally, 79.8% of conflux occurred at the bulbopontine sulcus, comparable to the Indians but much higher than in the Polish and Turkish populations. Therefore, females may be more susceptible to atherosclerosis of the VB junction.…”
Section: Epidemiologymentioning
confidence: 72%
“…This should assist prospective designs and utilization in diagnostic and interventional schemes. [23] VBS account for 37% of <2 cm cerebellar infarctions (CI) (small CI strokes), which frames 1/3 of the ISs in the posterior location, which most commonly involve the posterior lobe and occasionally the anterior and flocculonodular lobes with the favorable clinical outcome as compared to large CIs. [24] PCA territory is responsible for most embolic stroke of undetermined source, majorly subclinical atrial tachyarrhythmia.…”
Section: Epidemiologymentioning
confidence: 99%
“…The SCA typically originates from the basilar artery, as reported by most authors with a probability of 95-100%, a finding consistent with the results of this study. Additionally, the SCA may arise from the posterior cerebral artery in approximately 1.8% of cases, or sharing a common trunk with the posterior cerebral artery from the basilar artery, occurring in approximately 3.7% of cases [6,[10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all authors have reported cases of duplication of the SCA, with an average occurrence of 14%. Cases of bilateral duplication, triplication or absence of the SCA were much less common, with averages of 1.6%, 0.5%, and 0.9%, respectively [6,[10][11][12][13][14][15][16][17]. Note: BAbasilar artery; VAvertebral artery; * -Data is given as percentages (here and in Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Với PCoA là ĐM nhỏ nhưng có vai trò quan trọng, kết nối 2 hệ mạch chính cấp máu cho não là ICA và hệ sống-nền, đây là ĐM có tỉ lệ biến thể cao nhất trong số các ĐM được nghiên cứu, tỉ lệ không hiện ảnh trung bình là 21,65 trong đó bên trái là 22,6%; phải là 20,7%. Tỉ lệ hiện ảnh kém là 1,92%, theo H.M. Tú[3], tỉ lệ không hiện ảnh 2 bên là 30,39%; không hiện ảnh 1 bên là 15,68%, theo chúng tôi đây là tỷ lệ cao. Theo P.T.Hà[8], tỉ lệ này là 23,85% (52/218) khi nghiên cứu bằng MSCT và 10,55% khi nghiên cứu bằng DSA; A.Saha[9] khi nghiên cứu phẫu tích có 38,2% không thấy PCoA.…”
unclassified